2013
DOI: 10.1016/j.bbmt.2012.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Survival Differences between Adolescents/Young Adults and Children with B Precursor Acute Lymphoblastic Leukemia after Allogeneic Hematopoietic Cell Transplantation

Abstract: Risk adapted therapy has been the cornerstone of treatment for pediatric B-precursor acute lymphoblastic leukemia (B-ALL). Recently, age (>13 years at diagnosis) has been identified as a very high-risk feature for chemotherapy treated pediatric B-ALL patients. Whether age at time of transplant is associated with poor outcomes in adolescents and young adults (AYA) is unknown. We hypothesized AYA receiving allogeneic hematopoietic cell transplantation (allo-HCT) would have greater relapse and inferior survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 33 publications
3
35
1
Order By: Relevance
“…3,4 Given these findings, as well as our recent study showing inferior outcomes after allo-HCT for AYA patients with ALL, 10 we hypothesized that similar results would be present in AYA AML patients undergoing allo-HCT. In this analysis of 168 patients, including children and AYA with AML who received a myeloablative allo-HCT between 1995 and 2010, we identified no differences in survival or relapse between children and AYA patients.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…3,4 Given these findings, as well as our recent study showing inferior outcomes after allo-HCT for AYA patients with ALL, 10 we hypothesized that similar results would be present in AYA AML patients undergoing allo-HCT. In this analysis of 168 patients, including children and AYA with AML who received a myeloablative allo-HCT between 1995 and 2010, we identified no differences in survival or relapse between children and AYA patients.…”
Section: Discussionmentioning
confidence: 76%
“…These findings are in contrast to our AYA ALL patient outcomes treated in a similar period, where higher TRM was reported that negatively affected DFS. 10 The reasons for these differences are not entirely clear but may reflect the fact that patients with ALL receive considerably more chemotherapy compared with AML patients. The typical duration of treatment for patients with ALL is 2-3 years, compared with 5-6 months for patients with AML, which may contribute to greater overall organ toxicity and TRM reported in patients receiving allo-HCT for ALL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies specifically addressed outcomes among AYAs undergoing HCT (Burke MJ, BBMT 2013), and it is unclear whether the benefits of improvements in supportive care have been realized equally in the vulnerable AYA population. For these reasons, we sought to determine whether outcomes for AYAs following myeloablative allogeneic HCT for ALL have improved to a similar degree as those among older and younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to the infrequent use of allogeneic HSCT in pediatric populations, this procedure is often favored in AYAs with ALL. Yet the cumulative incidence of non-relapse mortality in patients aged greater thirteen years or older who have undergone allogeneic HSCT is as high as 28% [29]. Conversely, a meta-analysis that compared studies that treated AYA patients with ALL with either a pediatric-inspired regimen or a conventional adult chemotherapy regimen found that the cumulative rate of non-relapse mortality among patients that received a pediatric regimen was only 7% [30].…”
Section: Treatment and Outcomesmentioning
confidence: 94%